TINDAK TUTUR PADA CAPTION INSTAGRAM PRESIDEN JOKO WIDODO: KAJIAN PRAGMATIK - Endang Sumarti; Kingkin Puput Kinanti; Anita Kurnia Rachman (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Language functions as a media of communication and a media of delivering information. One of the most popular and popular social media is Instagram. Instagram is a social media that can be accessed easily and is useful as a means of providing information. The purpose of this research is to obtain an objective description of the form of speech acts and the functions of speech acts in President Joko Widodo's Instagram caption. This study uses a qualitative approach. The data source for this research is President Joko Widodo's Instagram Caption. The research data is in the form of quotes of words and sentences on President Joko Widodo's Instagram caption. Data was collected by reading technique, listening technique, and note taking technique. Furthermore, the data is classified based on its form and function and then analyzed using interactive model analysis techniques. Based on the results of data analysis, the following findings were obtained. First, the forms of speech acts on President Jokowi's Instagram caption include assertive speech acts, directive speech acts, expressive speech acts, commissive speech acts, and declarative speech acts. Second, the functions of speech acts in the caption of President Joko Widodo's Instagram include the functions of explaining, declaring, showing, ordering, asking, inviting, forbidding, thanking, expecting, congratulating, condolences, promising, and inaugurating.